Utilização do desmame precoce ou amamentação controlada no rebanho de cria em gado de corte - Moura, Ivan Cesar Furmann (2012)
The study was developed at Fazenda Modelo an Experimental Estation belonged to the Insituto Agronômico do Paraná (IAPAR) in the city of Ponta Grossa, Pr, in the period from June 2011 to March 2012. Aiming to evaluate the systems of early weaning and controlled nursing about the performance of cows and calves during the breeding season, 161 crossbred Purunã cows and their calves were used and the were divided into three groups: Early weaning (DP), which was fulfilled weaning of calves with the average age of 75 days; the group of controlled nursing (AC), the cows were separated from their calves and placed to breastfeed only once a day during the breeding season; and the third group was the conventional weaning (DC), which the cows kept their calves together during the whole time without any interference in the management, with definitive weaning at seven months. Cows from all groups calved in body condition score above 3.7 points (scale from 1 to 5), with no significant difference in the pregnancy rate, 90% for cows in DC, 96% for cows for AC and 97% for cows of early Weaning. When in good condition at calving the use of early weaning or controlled nursing do not bring productive benefitis, early weaning can cause decline in reproductive efficiency of the breeding herd because of the weight of the calf to be 19.6% lower compared to conventional weaning. Calves subjected to the DP showed a lower overage (P <0.05) daily weight gain (0.56 kg) during the experimental period compared to the group at the AC and DC (0.95 kg and 0.88 kg, respectively) which did not differ from each other (P <0.05). The management of controlled nursing causes no effect on the performance of calves, that can be weaned with similar weight to calves maintained together the cow. As the cow category (Young, Adult and Old) showed no interaction with the system weaning, they were discussed independently. It was observed that young cows are lighter (P <0.05) at calving and weaning of their calves (383.89 and 399.40 kg, respectively) compared to mature cows (444.07 and 451.92 kg) and old (452.35 and 470.49 kg). Therefore, the Heifers bred at two years old, that calve in good nutritional conditions have the same reproductive efficiency that adult cows (47.64 and 48.35 kg of weaning calf to 100 kg/cow, respectively), while the old cows show lower reproductive efficiency in a breeding herd (42.99 kg of calf per 100kg/cow). The lower weaning weight of calves born from primiparous and old is because of the lower weight and performance since the birth to 150 days of age, with no difference in performance after this period.